Best Practice Example, Erasmus+ Programme - Middleton, Nicos (My University, 2026)
Erasmus+ funded research programme "Baby Buddy Forward" (2017-2020) with N. Middleton (PI) has been denoted as "Best Practice Example" on the Erasmus+ Project Results Platform
Keywords: Service to society